Factors influencing capital structure of listed plantation companies in Malaysia / Sharifah Nursyafiqah Syed Abdul Jabar - Abdul Jabar, Sharifah Nursyafiqah Syed (Faculty of Business Management, 2017)
Capital structure refers to how firms finance their overall activities and run their business with multiple sources of financing such as debt and equity. There are many factors that could influence the capital structure of a firm. Therefore, this research is conducted to investigate the factors influencing the capital structure of listed plantation companies in Malaysia. The analysed factors could impact the indebtedness. The analysis is based on the panel data on a sample of 30 listed plantation companies, observed for the 5 year period, from 2012 to 2016. The dependent variable used in this study is debt ratio while the independent variables adopted in this study are profitability, tangibility, firm size, growth and liquidity. The method employed in this study is Ordinary Least Square (OLS) along with FixedEffect Model which is analysed using STATA software. The results show that liquidity, profitability and tangibility are negatively significant to the debt ratio. Negative relationship indicates that the increase of value in one variable will decrease the value of other variable. On the other hand, firm size shows positive relationship with debt ratio. Profitability is the most significant factor in this study. The results obtained in this study are mostly consistent with the results conducted by previous researchers on capital structure topic.